Impacto de la ansiedad y la depresión en el rendimiento académico en adolescentes y adultos emergentes - Carassas Medrano, Christian Walth (2024)
Anxiety and depression represent the psychosocial disorders with the highest prevalence in the adolescent and emerging adult population, impacting their academic performance. The purpose of this applied review was to examine the relationship between anxiety, depression, and academic performance, as well as inquire the directionality of this relationship, and examine the moderators’ variables that influence this interaction. A systematic search was conducted, following the PRISMA guidelines, consulting databases such as Scopus, Proquest, and Dialnet. Ten articles were selected for a detailed review to address the objectives. In light of this, a predominantly significant relationship with a negative directionality between these psychosocial disorders and academic performance was identified, demonstrating the impact between the variables. Additionally, two moderators’ variables were identified - peer support and perception of academic competence - which mitigated the negative impact of anxiety and depression on students' academic performance in a supportive manner. Finally, it is worth considering conducting longitudinal studies to elucidate the impact of variables over time, as well as conducting national-level studies and involving psychology professionals to further refine the obtained information.